Pengaruh Leverage, Likuiditas, Rasio Aktivitas dan Sales Growth Terhadap Financial Distress - Ni Made Adelia Putri; Luh Gede Sri Artini (Universitas 45 Surabaya, 2025)
Financial distress refers to a gradual decline in financial condition. This stage appears before the company faces the risk of bankruptcy or liquidation, which starts with the company's inability to meet its financial obligations. This study aims to test and analyze the effect of leverage, liquidity, activity ratio, and sales growth on financial distress. The research was conducted in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the period 2020 - 2023 with a total sample used of 23 companies or 92 total observations with the sample withdrawal method using the non probability sampling method. The data analysis technique uses logistic regression analysis using SPSS software. The results showed that the activity ratio variable had a negative and significant effect on financial distress in transportation and logistics sector companies, while the variables of leverage, liquidity and sales growth were not significant to financial distress. This shows that the smaller the value of total asset turnover increases the possibility of the company experiencing financial distress because it shows the company's inability to generate sales in proportion to the costs incurred for the assets it invests in.